Patients with self‐reported HS in a cohort of Danish blood donors. (1st April 2019) - Theut Riis, P.; Pedersen, O.B.; Sigsgaard, V.; Erikstrup, C.; Paarup, H.M.; Nielsen, K.R.; Burgdorf, K.S.; Hjalgrim, H.; Rostgaard, K.; Banasik, K.; Ullum, H.; Jemec, G.B.
Summary: Hidradenitis suppurativa (HS) is a distressing skin condition in which patients suffer from repeated eruptions of boils in the armpit, groin, under the breast, and in the perineum. The disease is suspected to affect around 1 in 100 people, but studies are conflicting on how many actually suffer from this disease. The unique nature of the disease makes it possible to diagnose the disease using questionnaires. Danish blood donors received the questionnaire, and 27, 765 answered it. Approximately 1.8 % (almost 1 in 50) of blood donors seemed to suffer from HS. Donors with HS had a higher body mass index and were younger than donors without; female to male ratio was approximately 1:1. Smoking frequency and body mass index of donors with HS were between that of blood donors without HS and patients with HS from other studies. The questionnaire also revealed that HS patients were more depressed, but their life quality was the same as non‐HS donors. The unique civil registration number in Denmark allowed us to compare publicly registered information about the participants. More HS donors received educational support and cash benefits (both are government support) than non‐HS donors. HS did not, however, seem to affect income of donors. Only 2.2 % of the HS donors were registered with the disease. We interpreted this as a need for better diagnosis of mild cases of the disease. If the blood donors continue to give blood, we can follow them to see how much their HS condition affects their life.